Additional prognostic value of the BCT score in ER+HER2- breast cancer patients receiving a 21-gene assay-guided adjuvant treatments - Ahn, Sung Gwe; Yu, Jonghan; Baek, Seung Ho; Kim, Yeon Jin; Kim, Woo Young; Chung, Jai Hyun; Bae, Soong June; Kim, Seok Won; Nam, Seok Jin; Gong, Gyungyub; Lee, Young-Won; Han, Jai Hong; et al. (Frontiers in Oncology, 2025)
BackgroundThe 21-gene recurrence score (RS)-guided decision-making for adjuvant treatment has been utilized as a standard of care for early ER+HER2- breast cancer. We investigated a prognostic value of the Breast Cancer Test (BCT) score, a multigene assay incorporating clinical risk, in estrogen receptor (ER)+HER2- breast cancer patients receiving RS-guided adjuvant treatments, specifically focusing on chemotherapy-untreated patients with low RS.MethodsThis multicenter cohort study included 759 patients who received RS-guided adjuvant treatment. The primary endpoint was recurrence-free survival (RFS), and the secondary endpoint was distant recurrence-free survival (DRFS).ResultsAt a median follow up of 85 months, the 7-year RFS was 92.9% (95% CI, 90.9%-94.9%). Among the 592 chemotherapy-untreated patients with low RS, the RFS differed significantly according to the BCT score (P=.014); the 7-year RFS was 95.5% (95% CI, 93.4%-97.7%) in the BCT-low group, while it was 89.9% (95% CI, 84.9%-95.1%) in the BCT-high group. The BCT score was an independent prognostic factor for both RFS and DRFS. In addition, the RFS of the low-BCT score group was superior to that of the high-BCT group in women aged 50 years or younger, with an RS of 16 to 25.ConclusionsOur study suggests the utility of the BCT score in stratifying the relapse risk among chemotherapy-untreated patients with a low RS, particularly in young women with an RS of 16–25 who are at risk for long-term recurrence.